Scaling Community Pharmacy Transformation with the 'Flip the Pharmacy' Implementation Model: Program Origins - Anne Marie Kondic; Troy Trygstad; Randy McDonough; Matt Osterhaus (University of Minnesota Libraries Publishing, 2020)
The rising costs of healthcare, increased chronic illnesses, and healthcare provider burnout has led to an environment desperate for scalable solutions to ease practice burdens. With a projected shortage in the number of primary healthcare providers available to provide team-based care, community-based pharmacy practitioners are accessible and eager to assist. In order to provide enhanced patient care services to aid their clinician colleagues, community-based pharmacists will have to transform their practices to support the provision of enhanced services and medication optimization in value-based payment models. The purpose of this article is to define how multiple factors in pharmacy, healthcare, technology and payment models aligned to create an opportunity for the Community Pharmacy Foundation and CPESN® USA to implement a nationwide community pharmacy practice model called 'Flip the Pharmacy'.  This new model aims to scale community pharmacy practice transformation and move beyond filling prescriptions at a moment-in-time to caring for patients over time through a 24-month step-wise program paired with in-person pharmacist coaching. Preliminary observations from the first six months of the program highlight community pharmacy as a site of care with community-based pharmacist practitioners providing and documenting targeted patient care interventions.    Article Type: Commentary